Analisis Sintaksis Penerjemahan Kitab Kuning Di Pesantren Shirotul Fuqoha’ Gondanglegi Malang - Widyawati, Erlik; Malikha, Usrin (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes the translation of yellow books at the Shirotul Fuqoha' Gondanglegi Islamic Boarding School, Malang, with a focus on syntactic challenges. A qualitative approach is used through observation and text analysis to understand and analyze the phenomenon of yellow book translation at the Shirotul Fuqoha' Gondanglegi Islamic Boarding School, Malang. The data obtained will be analyzed using qualitative descriptive analysis techniques with a focus on syntax. The researcher pays attention to elements such as subjects, predicates, objects, and the use of conjunctions in both languages. The results of the study indicate that the main challenge lies in the differences in sentence structure, the use of conjunctions, and word order between Arabic and Indonesian. This study emphasizes the importance of understanding the syntax of both languages in translation so that the translation results remain accurate and contextual.